Analysis of the Role of Digital Transformation in Increasing the Efficiency and Competitiveness of MSMEs at Mr. Sukadi's Super Tempe Factory - Asha Auria Daniswara; Rizka Nur Aini Febriyanti; Delfiana Permatasari (Takaza Innovatix Labs Ltd., 2026)
Digital transformation is a strategic step for Micro, Small, and Medium Enterprises (MSMEs) in improving operational efficiency and competitiveness in the information technology era. This study aims to examine the process, issues, and implementation of digital transformation at Pabrik Tempe Super Bapak Sukadi, an MSME located in Magelang City. The research approach used is qualitative descriptive with a case study method, through activities such as observation, business document analysis, and finally, interviews. The research findings indicate that the processes of financial recording, production, and marketing are still carried out manually, which can lead to potential errors in record-keeping. Nevertheless, the business owner has shown readiness to shift to a digital system and understands the importance of implementing a Management Information System.